CRY2 suppresses trophoblast migration and invasion in recurrent spontaneous abortion. (12th October 2019) - Wu, Lianzhi; Cheng, Biheng; Liu, Qian; Jiang, Ping; Yang, Jing
Abstract: Disruption of circadian rhythms is associated with aberrant trophoblast migration and invasion in recurrent spontaneous abortion (RSA). This study aims to explore the functional role and the mechanisms of cryptochrome 2 (CRY2), a fundamental component of the circadian clock, in regulating trophoblast migration and invasion. Human extravillous trophoblast cell line HTR-8/SVneo was used as a cell model. Cell migration and invasion were examined using wound healing assay and Transwell assay, respectively. The mRNA and protein levels were determined using quantitative real-time polymerase chain reaction and western blot, respectively. Luciferase reporter assay and chromatin immunoprecipitation assay were performed to explore the interaction between c-Myc to the brain and muscle ARNT-like protein 1 (BMAL1) promoter. CRY2 was highly expressed in human villous specimens of RSA. Furthermore, CRY2 overexpression impaired migration and invasion in HTR-8/SVneo cells, whereas CRY2 knockdown yielded the opposite results. Mechanistically, c-Myc bound to the BMAL1 promoter and induced BMAL1 transcription, both of which further activated matrix metalloproteinase 2/9 (MMP2/9) and facilitated migration and invasion in HTR-8/SVneo cells. CRY2 inhibited c-Myc-BMAL1 pathway and impaired migration and invasion of HTR-8/SVneo cells. Collectively, these findings demonstrate that CRY2 suppresses trophoblast migration and invasion via inhibiting c-Myc-BMAL1-MMP2/9 pathway.